Analisis Kepuasan Penggunaan Mesin Self Check-In Di Bandar Udara Internasional Yogyakarta – Kulonprogo - Nining Rika Anggela; Walid Jumlad (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
User satisfaction is a feeling obtained from previous expectations either to be better or very adequate in a service. Services using self check-in machines can simplify and shorten users or prospective passengers in carrying out their activities at the airport. In this study, the research objective was to find out the satisfaction of using a self check-in machine at Yogyakarta – Kulonprogo International Airport. The research entitled Analysis of Satisfaction Using Self Check-In Machines at Yogyakarta International Airport - Kulonprogo, was conducted by distributing questionnaires to users of self check-in machines at Yogyakarta International Airport. This research uses quantitative research methods. Data analysis techniques use the validity test, reliability test, and analysis to determine the average level of satisfaction. The results showed that satisfaction with the use of self check-in machines at Yogyakarta International Airport was high. Evidenced by the results of the evaluation for the conformity of expectations indicator obtaining an evaluation value of 4.39, the intention to reuse indicator obtaining an evaluation value of 4.2733, and the availability indicator recommending obtaining an evaluation value of 4.18.